Attitude towards English Slogan Used by Culinary Products of SMES and How It Affects Purchase Decisions - Gartika Rahmasari; Wawan Hendrawan (Jurnal Sekretaris dan Administrasi Bisnis, 2018)
This study examines the perception and comprehension of consumers towards 6 English slogans used by SMEs’ culinary product, particularly fruit-based crackers. Slogans examined include Aruna ( “Original taste and crispy”), Jecko ( “So crunchy), Matoh ( “Good things come to those who share”), Miun Chips ( “Indonesian sweet cassava chips”), Paradis Crunch (“Premium Indonesian banana chips”), and Zanana ( “Try it; Love it; Miss it.”). As a result, the most easy to understand English slogan considered by respondent is Aruna (“Original taste and crispy”) as much as 96,2%, and the most difficult slogan to understand is Matoh (“Good things come to those who share”) as much as 34,6%. In addition, slogans considered to be the easiest translated are Aruna and Zanana, where 100% of respondents stated that they were able to translate both slogans. However, when they were asked to translate all 6 slogans, it is slogan of Jecko which could be translated correctly by most, as much as 86,4%, and the most difficult slogan to translate is the slogan of Miun Chips. Also, Jecko has the slogan whose meaning is well understood by most of respondents, as much as 88,5 % respondents, and the slogan whose meaning is the most difficult to understand is the slogan of Miun Chips (30,8%). This study concluded that the use of English slogans by SMEs’ culinary product, despite how easy or difficult they are to be understood, did not affect buying decision. It is the package (46,2 %) and the taste of product (34,6%) that become the main reason for consumers to make buying decision, besides the price (15,4%) and halal sertificate (3,8%). Keywords: English Slogan, Purchase Decision, SME